(3efgL GdWdGH aj Yed GdESWQdGHs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjHdZ EPG MeOg GdMGeOhf adeG cGf GdGSWQdGH GTQa BdI hVYJ ai Yde Gdadc GMHHJ Gf GLeY ai Ydeg QSGdI ehVMI bQjHI GdeSdc s
(3BNQgG (B:s
(3hjcJH ai GdbSe GdPi jdjg U CNQi MJi jchf NW GdeZQH Hjf UGOjf GfJgi GdcdGe ai Yed QSGdJi GdGSWQdGH hGdJQLgGQ JeJ GdQSGFd s
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bhHdJ GdfSNI hUMMJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs